Conflict and Education Mapping the Field in Literature? - Shah, Habibullah (JOURNAL OF INDIAN EDUCATION, 2016)
The paper begins with the conceptualisation of the term ‘conflict’ for broader understanding of the field ‘conflict and education’. How literature has reflected on education as a victim of conflict is the first argument of this paper. This is followed by another argument; how education creates and promotes conflict. Then the paper also thoroughly discusses the role of education as an ambassador for peace in conflict settings. Lastly, we argue for a new area of inquiry that is currently omitted and underdeveloped within the field and that is, how conflict can have positive impact on education. This area in the field of education and conflict seems to have the potential to create a new discourse among theorists and practitioners for future research. That we call as Post Conflict Educational Growth and Development.